Women's preferences for contraceptive counseling and decision making - Dehlendorf, Christine; Levy, Kira; Kelley, Allison; Grumbach, Kevin; Steinauer, Jody (Contraception (Stoneham), 2013)
Little is known about what women value in their interactions with family planning providers and in decision making about contraception. We conducted semistructured interviews with 42 black, white and Latina patients. Transcripts were coded using modified grounded theory. While women wanted control over the ultimate selection of a method, most also wanted their provider to participate in the decision-making process in a way that emphasized the women's values and preferences. Women desired an intimate, friend-like relationship with their providers and also wanted to receive comprehensive information about options, particularly about side effects. More black and Spanish-speaking Latinas, as compared to whites and English-speaking Latinas, felt that providers should only share their opinion if it is elicited by a patient or if they make their rationale clear to the patient. While, in the absence of medical contraindications, decision making about contraception has often been conceptualized as a woman's autonomous decision, our data indicate that providers of contraceptive counseling can participate in the decision-making process within limits. Differences in preferences seen by race/ethnicity illustrate one example of the importance of individualizing counseling to match women's preferences.